2010
DOI: 10.1108/09526861011017102
|View full text |Cite
|
Sign up to set email alerts
|

Softer perspectives on enhancing the patient experience using IS/IT

Abstract: Purpose -This paper aims to argue that the implementation of the Choose and Book system has failed due to the inability of project sponsors to appreciate the complex and far-reaching softer implications of the implementation, especially in a complex organisation such as the NHS, which has multifarious stakeholders. Design/methodology/approach -The authors use practice-oriented research to try and isolate key parameters.These parameters are compared with existing conventional thinking in a number of focused are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The root cause of these ambiguities appears to be the heterogeneity of multiple stakeholders (Ojiako et al 2010). This, in turn, leads to a number of phenomena (such as aggregate reporting of performance, PMM being used for different purposes by different stakeholders and lack of awareness of each stakeholder's priorities).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The root cause of these ambiguities appears to be the heterogeneity of multiple stakeholders (Ojiako et al 2010). This, in turn, leads to a number of phenomena (such as aggregate reporting of performance, PMM being used for different purposes by different stakeholders and lack of awareness of each stakeholder's priorities).…”
Section: Discussionmentioning
confidence: 99%
“…It appears that, although the ESQ provides information that can be utilised in enhancing service quality, the reality is that user satisfaction does not imply improvements in quality of health outcomes; nor does it necessarily lead to effective service delivery (Maguire and Ojiako 2007;Ojiako et al 2010 Another context that led to fitness for purpose as a manifestation of ambiguity to be explored related to the requirement for CAMHS to collect information (for insurance purposes) which was predominantly financial, although its main service focus is on qualitative societal benefits linked to community-based challenges, e.g., social stigma. Of interest to this research is a view expressed by a clinical director (Interviewee 6) who suggested that the purpose of performance measures was:…”
Section: Fitness For Purpose Of the Performance Measurement And Manag...mentioning
confidence: 99%
“…Hence, in a similar light, productivity measures used in the current study were not related to acceptance equity which served as a measure of user receptiveness to the new technology. Earlier studies (Maguire, 2007;Maguire et al, 2010;Ojiako et al, 2010;Sooklal et al, 2011), suggest that not only are enterprise systems conceived decades prior to the commencement of introduction, but also that the relationship between the actors involved in systems development and the eventual adoption are unlikely to remain clear until well into the introduction/adoption process. Based on this, a comprehensive assessment of accrued benefits from enterprise systems are only to be realised after considerable re-adjustments within an organisation of not only its processes, but its structure and key competencies.…”
mentioning
confidence: 99%